Effectiveness Of Bamboo Panel In Reducing Sound - Shafei, Siti Nurbaini Mohd (Universiti Sains Malaysia, 2022)
Noise pollution is a dangerous hazard that is often overlooked. It is invisible to the naked eye, although it exists on land and beneath the water. It may also be described as any undesirable or distressing sound that has an impact on human and other species' health and well-being. Manufacturing, development, transportation, and community and home activities have all produced many types of noise in modern life. This research was conducted to investigate the effectiveness of bamboo panel as sound barrier. Beside, this study is carried out to compare the bamboo panel with other material as a sound barrier. The sound level meter are tool uses to measure the noise. Microsoft Excel are uses to calculate and generate table and graph for the study data. From the result obtain using bamboo panel and other materials as tool for the sound barrier, thus will generate comparable data of insertion loss. Insertion loss of sound are the sound that being reduce to lessen the noise pollution. This research then compare the result obtain from five different layer of the bamboo panel which is 1, 2, 3, 4 and 5 layer with other materials that is plywood, egg tray and polystyrene uses as sound barrier, and generate data on which data have the most insertion loss value. Thus, result to advise more suitable layer and distance for the bamboo panel.